The Information Technology & Communication and University Evaluation Indicators in Spain - Cardona Rodríguez, Antonio; Barrenetxea Ayesta, Miren (Education Policy Analysis Archives, 2003)
Since all institutions are reaffirming the importance of Information Technology and Communication (ICT) in education, but did you have this in mind when evaluating universities, Is reflected in the indicators for evaluation In Spain, as in other neighboring countries, universities are undergoing an institutional evaluation process. The catalog of indicators is a fundamental part of the assessment process. This paper is a brief analysis of the catalog of indicators proposed by the University Coordination Council in relation to its ability to measure the incorporation of ICT in universities.